Barriers to appropriate complementary feeding and the use of ultra‐processed foods: A formative qualitative study from rural Oromia, Ethiopia - Tadesse, Elazar; Abdirahman, Ibrahim; Letta, Shiferaw; Kirby, Miles; Mamo, Tigist; Metaferia, Henok; Oranga, Beryl; Leight, Jessica (Wiley, 2024)
Children's consumption of ultra-processed foods (UPF) is increasing in Ethiopia, but relatively little is known about the specific feeding practices that underlie this pattern. The objective of this study was to explore patterns of consumption of UPF by infants and young children within a broader context of inappropriate complementary feeding practices in extremely poor households in rural Oromia, Eastern Ethiopia. A formative qualitative study was conducted using semistructured interview questionnaires developed drawing on a socioecological model. A total of 16 focus group discussions with mothers (45 respondents), fathers (21 respondents) and grandmothers (23 respondents) of children aged 6–23 months in households that were beneficiaries of the Productive Safety Net Program were conducted, along with four key informant interviews with health workers. Qualitative transcripts were complemented with field notes before qualitative content analysis was applied. The key findings suggest that UPF were widely provided to infants and young children as part of a pattern of suboptimal complementary feeding, including both early and late initiation of complementary foods. In particular, UPF (including juice, biscuits and lipid-based nutrient supplements) were diluted with or dissolved in water and fed to infants via bottle, often before the recommended age of initiation of 6 months. Mothers and caregivers reported that they perceived the products to be affordably priced and packaged, ready to use and convenient given their time constraints. The level of consumption of UPF and its effects on infant and young child feeding feeding practices and children's nutritional status in rural Ethiopia should be further explored.